Syahrul Hidayat dan Fitri: Pengaruh Endorstment Dan Live Streaming Terhadap Keputusan Pembelian Pada E-Commerce Lazada Di Kota Makassar - Syahrul Hidayat; Fitri (LPPM STIEM BONGAYA, 2026)
“The Influence of Endorsement and Live streaming on Purchasing Decisions on Lazada E-commerce in Makassar City. Supervised by Jusri and Fitri. The purpose of this study was to determine and analyze, The influence of Endorsement on purchasing decisions on Lazada e-commerce, The influence of Live streaming on purchasing decisions on Lazada e-commerce, The influence of Endorsement and Live streaming on purchasing decisions on Lazada e-commerce, on Lazada consumer users in Makassar City. The method used in this study is quantitative. The population in this study were Lazada e-commerce users in Makassar City. The sampling technique in this study was by using the probability sampling technique with a sample size of 100 people with data analysis techniques using SPSS version 25 and using multiple linear regression analysis so that the relationship between variables could be determined. This study obtained the results that Endorsement (X1) had a positive and significant partial effect on purchasing decisions (Y), Live streaming (X2) had a positive and significant partial effect on purchasing decisions (Y). Endorsement (X1) and Live streaming (X2) have a positive and significant effect simultaneously on the purchase decision (Y) of e-commerce Lazada in Makassar City. Keywords: Endorsement; Live streaming; and Purchase Decision